Ancient ancestry of KFDV and AHFV revealed by complete genome analyses of viruses isolated from ticks and mammalian hosts. - Kimberly A Dodd; Brian H Bird; Marina L Khristova; César G Albariño; Serena A Carroll; James A Comer; Bobbie R Erickson; Pierre E Rollin; Stuart T Nichol (Public Library of Science (PLoS), 2011)
BACKGROUND: Alkhurma hemorrhagic fever virus (AHFV) and Kyasanur forest disease virus (KFDV) cause significant human disease and mortality in Saudi Arabia and India, respectively. Despite their distinct geographic ranges, AHFV and KFDV share a remarkably high sequence identity. Given its emergence decades after KFDV, AHFV has since been considered a variant of KFDV and thought to have arisen from an introduction of KFDV to Saudi Arabia from India. To gain a better understanding of the evolutionary history of AHFV and KFDV, we analyzed the full length genomes of 16 AHFV and 3 KFDV isolates. METHODOLOGY/PRINCIPAL FINDINGS: Viral genomes were sequenced and compared to two AHFV sequences available in GenBank. Sequence analyses revealed higher genetic diversity within AHFVs isolated from ticks than human AHFV isolates. A Bayesian coalescent phylogenetic analysis demonstrated an ancient divergence of AHFV and KFDV of approximately 700 years ago. CONCLUSIONS/SIGNIFICANCE: The high sequence diversity within tick populations and the presence of competent tick vectors in the surrounding regions, coupled with the recent identification of AHFV in Egypt, indicate possible viral range expansion or a larger geographic range than previously thought. The divergence of AHFV from KFDV nearly 700 years ago suggests other AHFV/KFDV-like viruses might exist in the regions between Saudi Arabia and India. Given the human morbidity and mortality associated with these viruses, these results emphasize the importance of more focused study of these significant public health threats.